2021
DOI: 10.1111/nph.17571
|View full text |Cite
|
Sign up to set email alerts
|

Towards a statistically robust determination of minimum water potential and hydraulic risk in plants

Abstract:  Minimum water potential ( min ) is a key variable to characterize dehydration tolerance and hydraulic safety margins (HSM) in plants.  min is usually estimated as the absolute minimum tissue  experienced by a species, but this is problematic because sample extremes are affected by sample size and by the underlying probability distribution. We compare alternative approaches to estimate  min and assess the corresponding uncertainties and biases; propose statistically robust estimation methods based on ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Here, we used TLP‐based HSM to explore how drought tolerance is associated with the other trait axes. This was because (1) Ψ min was less abundant than TLP in our dataset (Table 1), (2) Ψ min field data may be affected by sampling protocol (Martínez‐Vilalta et al, 2021) and (3) TLP‐based HSM recently proved to be highly indicative of observed drought‐induced mortality rates (Martin‐StPaul et al, 2017; Powers et al, 2020). However, we included Ψ min and Ψ min ‐based HSM in our exploration of how drought tolerance traits are coordinated.…”
Section: Methodsmentioning
confidence: 92%
“…Here, we used TLP‐based HSM to explore how drought tolerance is associated with the other trait axes. This was because (1) Ψ min was less abundant than TLP in our dataset (Table 1), (2) Ψ min field data may be affected by sampling protocol (Martínez‐Vilalta et al, 2021) and (3) TLP‐based HSM recently proved to be highly indicative of observed drought‐induced mortality rates (Martin‐StPaul et al, 2017; Powers et al, 2020). However, we included Ψ min and Ψ min ‐based HSM in our exploration of how drought tolerance traits are coordinated.…”
Section: Methodsmentioning
confidence: 92%
“…At the same time, tracheid's formation is strongly influenced by Ψmin, as low pressures result in reduced cell expansion and thus lower lumen areas, increasing wood density. These relationships could explain the strength of the RWI‐SPEI relationship covariation with WD and Ψmin, although species‐level Ψmin values should be interpreted with caution (Martínez‐Vilalta et al, 2021). Ψmin is associated with atmospheric vapour pressure deficit, soil water potential, water use regulation and tree architecture (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This bias could be related to an under-estimation of negative ψ min at wetter sites owing to lower sampling of rare dry days at such sites compared to more frequently occurring dry days at drier sites. Plants at wetter sites may be adapted to infrequent drought events which may be missed in the sampling of ψ min (Martinez Vilalta et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%